Development of Tourism Villages Through Village-Owned Enterprises (BUMDes) to Increase Community Income in Bagot Parlondut Tourism Village Samosir North Sumatera - Revida, Erika; Badaruddin (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The community service Professor Serving USU 2022 aims to educate the community in the tourist village of Bagot Parlondut Samosir North Sumatera. The title of community service was Development of tourism villages through village-owned enterprises (BUMDes) to increase community income. The aim of community service was to increase the knowledge of village owned enterprises’ managers, especially how to manage tourism villages to increase the community income. Metode of community service was counselling, workshop and attraction for making Bagot cakes. On the first day, a meeting was held with the village head. Tourism Village Owned Enterprises management, community leaders in the tourist village of Bagot Parlondut Samosir, North Sumatera. The material presented was about the importance of community service activities for the tourism village community of Bagot Parlondut North Sumatera, especially the use of Village Owned Enterprises to develop a tourism village. The second day, held an education, workshop on the development of tourist villages through Village Owned Enterprises to increase community income, and the activity ended with the attraction of making Bagot cakes. The result of community service showed that the community had a positive response and enthusiasm in participating in the activities and asking questions related to the development of the ourist village through Village Owned Enterprises (BUMDes). They hope that in the future the community service will not stop at the time, but will continue so that they gain more knowledge about how to increase tourism through village owned enterprises (BUMDes). The community service ended with the giving gifts to the teams of Community service Professor community 2022 and taking photos.